Five centuries after the introduction of the Castilian pigeon (Columba livia Gmelin, 1789) in Peru - Pulido , Victor (2023)
The Castile pigeon (Columba livia Gmelin, 1789), native to Africa and Eurasia, is widely distributed in most of Europe, western Asia, Africa and America. Columba livia was introduced to Peru by the Spanish in the 16th century. It lives in urban and rural areas; in recent decades its population has grown exponentially around the world; it is considered to be a commensal species of the human being and in some cases in the cities it colonizes, it causes damage to the infrastructure and constitutes a risk to public health. Although its origin is wild, it behaves as one of the species with the greatest interaction with humans. The increase in its population in cities has turned it into a pest species. This review describes the current state of knowledge of Columba livia populations, its possible effects on the health of the human population, public ornamentation and the analysis of its status as an invasive exotic species, five centuries after its introduction into the Peru.